On the identity of Cryptocoryne pygmaea (Araceae) from Western Mindanao and the description of a new species from the islands of Palawan and Busuanga - Naive, Mark Arcebal K.; Bastmeijer, Jan D.; Jacobsen, Niels (Phytotaxa, 2022)
Recent fieldwork in Zamboanga del Norte resulted in the recollection of the poorly known aquatic aroid, Cryptocoryne pygmaea. In this study, we have clarified the identity of C. pygmaea as well as provided a detailed morphological description based on our recently collected material, updated its geographical distribution information, ecology, phenology, and a proposed conservation status. Through this recollection, it was revealed that plants previously identified as C. pygmaea in Palawan and Busuanga are different, thus we describe them here as C. palawanensis, a species new to science and the eighth representative of the genus for the Philippine archipelago.